2021
DOI: 10.3892/or.2021.8094
|View full text |Cite
|
Sign up to set email alerts
|

Pinosylvin inhibits migration and invasion of nasopharyngeal carcinoma cancer cells via regulation of epithelial‑mesenchymal transition and inhibition of MMP‑2

Abstract: Nasopharyngeal carcinoma (NPC) is a tumor located in the nasopharynx with highly invasive and metastatic properties. Metastasis is a primary cause of mortality in patients with NPC. The terpenoid polyphenol pinosylvin is a known functional compound of the Pinus species that exhibits anti-inflammatory effects; however, the effect of pinosylvin on human NPC cell migration and invasion is unclear. The present study aimed to investigate the functional role of pinosylvin in NPC cells (NPC-039… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…29,46 Studies also have shown that PIN can inhibit the growth of human colorectal cancer cell migration and invasion of nasopharyngeal carcinoma cancer cells. 47,48 These findings further support our view.…”
Section: Discussionsupporting
confidence: 90%
“…29,46 Studies also have shown that PIN can inhibit the growth of human colorectal cancer cell migration and invasion of nasopharyngeal carcinoma cancer cells. 47,48 These findings further support our view.…”
Section: Discussionsupporting
confidence: 90%
“…Western blotting was performed per a previously described method [ 57 ]. In brief, KHYG-1 and K562 cells were treated with shuterin for 24 h and then lysed using radioimmunoprecipitation assay buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Attaining invasiveness may be the main cause of malignant transformation, metastasis, and postoperative recurrence of meningiomas ( Banan et al, 2021 ; Jalali et al, 2015 ). In fact, for most cancers, inhibition of tumor cell invasion is considered to be an effective and fundamental strategy to combat malignant progression ( Chuang et al, 2021 ; Zhang et al, 2020a ). Inhibition of the regulatory factors related to meningioma cell invasion may effectively inhibit the proliferation and survival of meningioma cells ( Tummalapalli et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%